Electroplating of Zn at different current densities onto mild steel for improved corrosion resistance. (2022) - Upadhyay, Pundrikaksha; Das, Sanjeev; Basu, Anindya; Mallik, Archana
Abstract: The main objective was to replace hot-dip galvanization technique with electro-galvanization so as to reduce thickness of coating and also to do away with problem of heat affected zone arising in hot dip galvanization, further enhancing the corrosion resistance of electro-galvanized coating by using alloying elements. Pure Zinc was electrodeposited on mild steel (MS) sample at specific current densities i.e. at −50, −150, −250 mA/cm 2 from sulphate bath and its characterization was done by various techniques. The deposition current/ potential obtained by a systematic cyclic voltammetry study. Corrosion rate of coating was found using potentio-dynamic polarization technique and corrosion mechanism was obtain by Electrochemical Impedance Spectroscopy (EIS) analysis. Thickness of coating was measured using surface profilometer and was found to be in the range of 13 µm to 29 µm. Scanning electron microscopy (SEM) images and X-ray diffraction (XRD) data were taken and analyzed and finally corrosion rate was calculated using tafel extrapolation. Best corrosion result was found at −150 mA/cm 2 current density. The corrosion resistance of coating was slightly increased and also coarse grain structure was obtained when SEM images were compared.